Pengaruh Exercise Shuttle Run Dalam Peningkatan Kelincahan Pada Atlet Sepak Bola Di Academy Ads Tangerang - Yulis Susanti; Putri Dhea Oktaviani (CV. KAMPUS AKADEMIK PUBLISHING, 2024)
One of the physical conditions that a soccer player must have is agility. Agility is the body's ability to be able to change the direction of movement and body position quickly and without having to lose balance. So in a soccer game every athlete or player is required to be able to move quickly, precisely and agilely in order to get past the obstacles faced by the opponent. The research design used is Pre-Experimental Design with the OneGroup Pretest-Posttest Design model. The results of the Paired T-Test bivariate test showed that Asymp.Sig. (2-tailed) after being given the intervention obtained results <0.01 where the results obtained <0.05 from the results of the hypothesis obtained there is a difference or influence on the intervention given to agility in soccer athletes at Academy ADS Tangerang so that Ha is accepted and H0 is rejected. The results of the bivariate test analysis using the normality test showed an increase in the Illinois Agility Test score before and after the Shuttle Run intervention with normally distributed results and continued with the hypothesis test using the Paired T-Test test where the resulting hypothesis was that there was an effect on the intervention (Ha accepted). So the provision of Shuttle Run intervention affects the agility of soccer athletes at Academy ADS Tangerang